Demand Side Management Implementation in Downstream Digestate Treatment of a Biomethane Biorefinery - Röder, Lilli Sophia; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Chemical Engineering Transactions)

Experimentelle Untersuchung und Modellvalidierung zur Gravidestillation - Wende, Marc; Fischer, Florian; Kenig, Eugeny (Jahrestreffen der ProcessNet Fachgruppen Fluidverfahrenstechnik und Hochdruckverfahrenstechnik)

Heat regeneration model for external heat engines operating with dense working fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny (Annual Meeting on Reaction Engineering and ProcessNet Subject Division Heat and Mass Transfer)

Innovative Leichtbau- und Kühlungskonzepte für elektrische Maschinen durch additive Fertigung (ILuKadd3D) - Haase, Michael; Tasche, Frederik; Bieber, Maximilian; Zibart, Alexander

Entwicklung eines innovativen Trennapparates zur Stickstoffrückgewinnung aus landwirtschaftlichen Abfällen - Bernemann, Sören Antonius; Maćkowiak, Jan; Maćkowiak, Jerzy; Bertling, René; Lutters, Nicole; Kenig, Eugeny

An explicit symplectic approach to solving the wave equation in moving media - Inguva, Venkatesh; Feldmann, Nadine; Claes, Leander; Koturbash, Taras; Hahn-Jose, Thomas; Koutcherov, Vladimir; Kenig, Eugeny (Engineering Reports)
An explicit approach using symplectic time integration in conjunction with traditional finite difference spatial derivatives to solve the wave equation in moving media is presented. A simple operator split of this second order wave equation into two coupled first order equations is performed, allowing these split equations to be solved symplectically. Orders of symplectic time integration ranging from first to fourth along with orders of spatial derivatives ranging from second to sixth are explored. The case of cylindrical acoustic spreading in air under a constant velocity in a 2D square structured domain is considered. The variation of the computed time-of-flight, frequency, and wave length are studied with varying grid resolution and the deviations from the analytical solutions are determined. It was found that symplectic time integration interferes with finite difference spatial derivatives higher than second order causing unexpected results. This is actually beneficial for unstructured finite volume tools like OpenFOAM where second order spatial operators are the state-of-the art. Cylindrical acoustic spreading is simulated on an unstructured 2D triangle mesh showing that symplectic time integration is not limited to the spatial discretization paradigm and overcomes the numerical diffusion arising with the in-built numerical methods which hinder wave propagation.

Untersuchung von Gefahrensituationen bei industriellen Absorption/Desorption-Prozessen mittels dynamischer Simulation - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny Y.

Development of an innovative separation unit for nitrogen recovery from agricultural waste - Bernemann, Sören Antonius; Maćkowiak, Jan; Maćkowiak, Jerzy; Bertling, René; Lutters, Nicole; Kenig, Eugeny
Keywords: CFD; simulation; agricultural waste; multiphase

A Thermal Model for Recuperative Heat Engines Operating with Dense Working Fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Inguva, Venkatesh; Kenig, Eugeny Y. (1st Conference on Energy, Environment and Digital Transition E2DT)

Effect of diffusivity and chemical reactions on the determination of mass transfer coefficients in columns with structured packing - Mapura, Luz Alejandra; Kenig, Eugeny Y. (Annual Meeting on Reaction Engineering and ProcessNet Subject Division "Heat and Mass Transfer")

Experimental study on the condensation of pure substances in outer pillow-plate channels - Buckmann, Felix; Kenig, Eugeny (Annual Meeting on Reaction Engineering and ProcessNet Subject Division "Heat and Mass Transfer")

Liquid flow morphology investigation in structured packings for offshore applications using a novel flow imaging sensor - Mamedov, Tural; Schleicher, Eckhard; Schubert, Markus; Ehlert, Thomas; Kenig, Eugeny Y.

Untersuchung von kleinskaligen Flüssigkeitselementen auf mikrostrukturierten Packungsoberflächen - Dechert, Christopher; Kenig, Eugeny

A Thermal Model for Recuperative Heat Engines Operating with Dense Working Fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Inguva, Venkatesh; Kenig, Eugeny Y. (Chemical Engineering Transactions)

CFD-Based Investigation of the Packing Microstructure Influence on Droplet Behavior and Film Flow - Dechert, Christopher; Kenig, Eugeny (Proceedings of the 12th international conference Distillation & Absorption 2022)

On Heat Regeneration Limitations in Heat Engines With Dense Working Fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny (Heat Powered Cycles Conference 2022)

Modellierung des Stofftransportes in einer geneigten Kolonne mit dem Ansatz der hydrodynamischen Analogien - Ehlert, Thomas; Mamedov, Tural; Schubert, Markus; Kenig, Eugeny Y.

Dynamic modeling of absorption/desorption closed-loop including periphery - Bothe, Mike; Hami Dindar, Iman; Lutters, Nicole; Kenig, Eugeny Y. (Computers and Chemical Engineering)

A PLIC-based method for species mass transfer at free fluid interfaces - Schulz, Andreas Markus; Wecker, Christian; Inguva, Venkatesh; Lopatin, Alexey S.; Kenig, Eugeny Y. (Chemical Engineering Science)

Droplet formation –a numerical investigation of liquid-liquid systems with consideration of Marangoni convection - Wecker, Christian; Schulz, Andreas Markus; Heine, Jens; Bart, Hans Jörg; Kenig, Eugeny Y. (International Journal of Heat and Mass Transfer)